Helicobacter (Campylobacter) pylori and Acid Peptic Diseases - Sigmund Kradjen; Philip Sherman (Canadian Journal of Gastroenterology)
Helicobacter pylori is a spiral-shaped Gram-negative bacteria implicated as a cause of histological gastritis, contributing to peptic ulcer disease and perhaps playing a role in gastric cancer in humans. The organism is found worldwide; the prevalence of infection increases with age; and colonization probably persists for life. Diagnostic approaches chat have been used include tissue stains, culture of stomach biopsy specimens, labelled-urea breath tests and serology. It is too early to advocate treatment for all infected individuals; the benefits and risks have yet to be carefully studied and assessed.